Land[e]scapes (part II), International Group Exhibition, curated by Maria Stathi - Pericleous, Vicky (My University, 2024)
Art Seen is pleased to present the second part of the group exhibition 'Land[e]scapes' opening on the 29th of May 2024. The show is curated by Maria Stathi. 'Land[e]scapes' explores our relationship with nature, geology, topos, and time. The exhibition features select artists whose creations awaken new realms of contemplation about landscape. Participating artists: Chris Akordalitis, Panayiotis Andreou, Serena Caulfield, Benjamin Deakin, Marina Genadieva, Andreas Kalli, Kyriakos Kallis, Nicolas Kyrillou, Panayiotis Michael, Vicky Pericleous, Nicos Philippou & Marilena Zackheos, Amy Stephens, Korallia Stergides, Amikam Toren, Vassia A. Vanezi, Shaheer Zazai and Vasilis Zografos. At the heart of the exhibition lies the concept of "landscape" as a multifaceted construct, embodying social, cultural, and environmental narratives. “Landscape” serves as a canvas upon which personal, political, and societal attitudes are etched and reflected. Various elements of landscape—vegetation, expanses of land, bodies of water, rock and mountain formations—manifest in diverse artistic mediums, serving as conduits for exploration into our relationship with nature and the formation of our identity. Moreover, landscapes not only speak of nature but also bear the imprint of the artists and the cultural and historical contexts in which they were created. In contested territories or geographical areas that have witnessed conflict, war, colonialism, natural disasters, forced migrations or the effects of climatic change, the cultural and historical contexts are especially relevant in the reimagining of landscape. In the exhibits on display, the visitor will encounter environmental sensitivities, fascinations with geology, examinations of how war alters land, symbolic journeys to lost homelands, intercontinental travels, childhood memories, edenic utopias, and mythological places. Each of these unique explorations of landscape unveils portals to both real and alternate realms.
From the Series: Studies for a Place, Proposition X, 2024, Vicky Pericleous, ceramic, fossils, semi-precious stones, industrial tiles, 102 x 61 x 8 cm.
From the Series STUDIES FOR A PLACE: IV, 2023, Vicky Pericleous, collage, print on reflective aluminium, variable
Keywords: Arts; Landscape; Space; Nature; Geology; Topos; Time; Construct; Identity; Colonialism; Migration; Climate Change